ENT300 : Fundamentals Of Entrepreneurship Museum of Pizza / Nur Fathin Amira Sapawi... [et.al] - Sapawi, Nur Fathin Amira; Tengku, Peggy; Hamli, Nur Aisyah; Zolpata, Syazwani (2015)
Business plan is very crucial for everyone who wants to start a new business. Without a business plan, the organization will not be organized as it consists of the activities, strategy, financial operation and others that are related to the business. The business plan acts as a guideline to help entrepreneurs who are new in the business world. Museum of Pizza is a partnership business which ventures and major with the goods of our main menu, Pizza and also services of delivering the pizzas to our customers. Our business is mainly targeted to all ages of generation. The business is in the form of enterprise which consists of four shareholders. All shareholders have agreed as stated in agreement letter which the amount of capital, profit and loss will be divided as stated ratio. We have chosen this kind of business because it shows the equality and no one will be discriminated as the profits and losses are equally divided in the end of the accounting period.